Penjabat Kepala Daerah dan Tantangan Demokrasi Lokal - Fikri, Ahmad Fatkul (Universitas Medan Area, 2025)
The implementation of the 2024 Simultaneous Regional Elections in Indonesia has led to a leadership vacuum in 271 regions, which must be filled by Acting Regional Heads (Pj KDH). The top-down and non-transparent appointment of Pj KDH has triggered public controversy, conflicts of interest, and weakened both legal legitimacy and local democracy. This study aims to analyze the problems, key issues, and alternative solutions in the appointment of Acting Regional Heads. Employing a critical discourse analysis method with Norman Fairclough’s three-dimensional framework—textual analysis, discourse practice, and socio-political context—the research draws on diverse data sources, including audio-visual materials (YouTube, Instagram, Zoom meetings), academic journals, laws and regulations, as well as online and print media. The findings reveal that the non-transparent and non-participatory appointment of Pj KDH contributes to the decline of democratic practices, bureaucratic politicization, and conflicts of interest involving acting officials, local parliaments (DPRD), and civil servants. This study recommends the establishment of clear technical regulations governing the selection process, the involvement of local parliaments, the formation of independent selection committees, and the prioritization of appointing regional secretaries (Sekda) as acting heads.